Impact of psoriatic arthritis and comorbidities on ustekinumab outcomes in psoriasis: a retrospective, observational BADBIR cohort study - Alexis Ogdie; William Tillett; Alun Passey; Patricia Gorecki (RMD Open, 2023)
Objectives Psoriasis and psoriatic arthritis (PsA) are independently associated with comorbidities, including obesity and metabolic syndrome, which may impact treatment outcomes. This study aimed to assess baseline differences between patients with plaque psoriasis alone and those with concomitant PsA, and to investigate the impact of these characteristics on ustekinumab (UST) persistence and outcomes.Methods 9057 patients receiving UST or conventional systemic disease-modifying antirheumatic drugs were selected from the British Association of Dermatologists Biologic and Immunomodulators Register. The psoriasis and PsA cohorts were compared at baseline. Time to discontinuation during 10-year follow-up was assessed using multivariable Cox regression and Kaplan–Meier analyses, stratifying for interacting covariates and PsA status. Generalised linear mixed models assessed the impact of baseline characteristics on Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index over time.Results Greater comorbidity burden, including hypertension, diabetes, obesity and depression, and greater inability to work were observed in the PsA cohort than in the psoriasis cohort. PsA (HR 1.98), female sex (HR for male sex 0.72) and depression (HR 1.21) were associated with shorter UST persistence. PsA showed a differential association with UST persistence by PASI strata and prior biologic exposure. Quality of life was negatively impacted by depression and PsA.Conclusions The negative impact of comorbidities on treatment persistence identified in this study emphasises the need for patient-centric, multidisciplinary care in screening for and managing comorbidities in psoriasis and PsA treatment. Psychological support and lifestyle management of modifiable risk factors, including obesity, should be considered.